Influencia do armazenamento de manivas de mandioca (Manihot esculenta Crantz) na producao de raizes e ramas - Luna R., J.M.; Correa, H.; Leihner, D.E. (1986)
The effects of cutting storage on cassava root and branch production as well as on other crop characteristics (wt. loss, percentage of viable cuttings, sprouting 80 days after planting, final stand, no. of seed- cuttings/plant) were studied under field conditions in the banana growing zone of Santa Marta (Magdalena, Colombia) between Feb. 1982 and April 1983. Cuttings were stored with and without chemical treatment (benomyl and captan at 3000 ppm each) in horizontal and vertical positions for periods of 0, 30, 60, and 90 days. Cuttings 20 cm long were spaced at 1 x 1 m on ridges, planted in vertical position at a depth of 10 cm. A split- plot exptl. design with 6 replicates was used. Cuttings stored in a vertical position tolerated 90 days of storage with only minor losses in FW. Sprouting 80 days after planting and final stand were least affected when cuttings were treated chemically. The highest no. of commercial cuttings/plant was obtained without chemical treatment and a storage duration of 90 days. Root production was not affected by chemical treatment, storage position or duration. (AS)